Microbiological Characterization for a New Wild Strain of Paenibacillus Polymyxa with Antifungal Activity Against Botrytis Cinerea - Castillo-Nara, A; Huilinir-Curio, C; Cottet-Bustamante, L (Academic Press, 2016)
A new bacterial strain with powerful antifungal activity against the phytopathogenic fungus Botrytis cinerea was characterized and identified as Paenibacillus polymyxa SCHC33. The kinetics of bacterial growth was fitted to the Monod model, with μmax = 0.218 h−1, Ks = 0.087g/L, and YX/S = 0.159 g dry biomass/g glucose. The antifungal activity of the bacterium was detected in vitro as inhibition halos in antagonism bioassays against B. cinerea, and such activity was unchanged in magnitude when the assays were done in the same culture media with or without glucose. The ability of the bacterium to protect grapevine leaves against B. cinerea attack was determined as the percentage of damage to the plant tissue, after inoculation with different ratios of conidia and bacteria. Approximately 88% of the leaf surface was protected by the bacteria when a ratio of conidia:bacteria = 1:100 was used. No significant damage was observed in the tissue of the leaves inoculated only with bacteria, whereas the leaves that were treated with solely conidia, the necrotic damage occurred in approximately 100% of their surface. Therefore, the results indicate that P. polymyxa SCHC33 has great potential to become the active component of a new biofungicide for control of B. cinerea. © 2016 Elsevier Inc.